2002
DOI: 10.1046/j.1469-8137.2002.00360.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of hydrophobins DGH1, DGH2 and DGH3 and immunolocalization of DGH1 in strata of the lichenized basidiocarp of Dictyonema glabratum

Abstract: Summary• The expression of hydrophobin genes DGH1 , DGH2 and DGH3 in the lichenized fruitbody of Dictyonema glabratum (syn. Cora pavonia ) is reported here, as well as immunolocalization of the DGH1 protein.• In situ hybridization was conducted to determine expression patterns of hydrophobin genes DGH1 , DGH2 and DGH3 . The DGH1 protein was expressed in Escherichia coli and used to raise antibodies for immunolocalization of the DGH1 protein.• DGH1 and DGH2 are expressed by hyphae in the photobiont layer and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 37 publications
(84 reference statements)
0
28
0
Order By: Relevance
“…It is possible that the 18-and 22-kDa proteins may be dimers of the smaller proteins. In situ hybridization studies showed that DGH1, DGH2, and DGH3 are expressed by the D. glabratum mycobiont and not by the photobiont (Trembley et al, 2002). That many hydrophobins are expressed in D. glabratum is not surprising considering the complexity of the fruitbody and that differently aged tissues and various stages of differentiation coincide within.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the 18-and 22-kDa proteins may be dimers of the smaller proteins. In situ hybridization studies showed that DGH1, DGH2, and DGH3 are expressed by the D. glabratum mycobiont and not by the photobiont (Trembley et al, 2002). That many hydrophobins are expressed in D. glabratum is not surprising considering the complexity of the fruitbody and that differently aged tissues and various stages of differentiation coincide within.…”
Section: Discussionmentioning
confidence: 99%
“…Diploschistes muscorum is a stratified lichen. Lichens with this type of anatomy tend to have, even when fully hydrated, many air filled spaces in their inner thalli due to presence of hydrophobic molecules that prevent waterlogging (Lange et al 1997;Trembley et al 2002;Lakatos et al 2006). The presence of such spaces would decrease water replenishment via capillary action.…”
Section: Discussionmentioning
confidence: 99%
“…For example, they have been shown to be involved in Magnaporthe oryzae conidiogenesis and appressorium formation (Talbot et al 1993(Talbot et al , 1996, Cladosporium fulvum spore dispersal (Whiteford and Spanu 2001), Dictyonema glabratum maintenance of air channels in fruiting bodies and lichen thalli (Trembley et al 2002), Tricholoma terreum mycorrhizal formation (Mankel et al 2002), and Schizophyllum commune aerial hyphae formation and ability to attach to hydrophobic surfaces (Van Wetter et al 1996;Wösten et al 1994). In addition, they are involved in resistance to killing by host aveolar macrophages in the human pathogen Aspergillus fumigatus (Paris et al 2003), microsclerotia development in Verticillium dahliae (Klimes and Dobinson 2006), basidiocarp diVerentiation of the mushroom Agrocybe aegerita (Santos and Labarère 1999), mycelial growth after induction of fruiting and during fruiting body initiation in Flammulina velutipes (Ando et al 2001), and in formation of Pisolithus albus ectomycorrhizaes (Dublessis et al 2001) and Fusarium verticillioides microconidia (Fuchs et al 2004;Li et al 2006).…”
Section: Introductionmentioning
confidence: 99%